Impact of “Raised without Antibiotics” Beef Cattle Production Practices on Occurrences of Antimicrobial Resistance - Vikram, Amit (Appl Environ Microbiol, 2017)
The specific antimicrobial resistance (AMR) decreases that can be expected from reducing antimicrobial (AM) use in U.S. beef production have not been defined. To address this data gap, feces were recovered from 36 lots of “raised without antibiotics” (RWA) and 36 lots of “conventional” (CONV) beef cattle. Samples (n = 719) were collected during harvest and distributed over a year. AMR was assessed by (i) the culture of six AM-resistant bacteria (ARB), (ii) quantitative PCR (qPCR) for 10 AMR genes (ARGs), (iii) a qPCR array of 84 ARGs, and (iv) metagenomic sequencing. Generally, AMR levels were similar, but some were higher in CONV beef cattle. The prevalence of third-generation cephalosporin-resistant (3GC(r)) Escherichia coli was marginally different between production systems (CONV, 47.5%; RWA, 34.8%; P = 0.04), but the seasonal effect (summer, 92.8%; winter, 48.3%; P < 0.01) was greater. Erythromycin-resistant (ERY(r)) Enterococcus sp. concentrations significantly differed between production systems (CONV, 1.91 log(10) CFU/g; RWA, 0.73 log(10) CFU/g; P < 0.01). Levels of aadA1, ant(6)-I, bla(ACI), erm(A), erm(B), erm(C), erm(F), erm(Q), tet(A), tet(B), tet(M), and tet(X) ARGs were higher (P < 0.05) in the CONV system. Aggregate abundances of all 43 ARGs detected by metagenomic sequencing and the aggregate abundances of ARGs in the aminoglycoside, β-lactam, macrolide-lincosamide-streptogramin B (MLS), and tetracycline AM classes did not differ (log(2) fold change < 1.0) between CONV and RWA systems. These results suggest that further reductions of AM use in U.S. beef cattle production may not yield significant AMR reductions beyond MLS and tetracycline resistance. IMPORTANCE The majority of antimicrobial (AM) use in the United States is for food-animal production, leading to concerns that typical AM use patterns during “conventional” (CONV) beef cattle production in the United States contribute broadly to antimicrobial resistance (AMR) occurrence. In the present study, levels of AMR were generally similar between CONV and “raised without antibiotics” (RWA) cattle. Only a limited number of modest AMR increases was observed in CONV cattle, primarily involving macrolide-lincosamide-streptogramin B (MLS) and tetracycline resistance. Macrolides (tylosin) and tetracyclines (chlortetracycline) are administered in-feed for relatively long durations to reduce liver abscesses. To ensure judicious AM use, the animal health, economic, and AMR impacts of shorter duration in-feed administration of these AMs should be examined. However, given the modest AMR reductions observed, further reductions of AM use in U.S. beef cattle production may not yield significant AMR reductions beyond MLS and tetracycline resistance.